The concept of benefit sharing in the context of the eastern Nile Basin - Fetene, M. (Addis Ababa University, 2009)
This study attempted to predict the likely impacts of a dam reservoir and flow regulation on riparian plant composition and diversity. The study was conducted around the Koga dam in the upper part of the Blue Nile basin in the northwestern part of Ethiopia. Floristic composition and diversity in the riverine and adjacent sites of the river was studied. The presence of plant species that would be affected by the storage of the Koga River water and the modification of the downstream river flow regime were assessed. A total of 87 plots (3.48 ha) were laid, of which 57 (2.28 ha) were located in the upstream area, 17 (0.68 ha) in the vicinity of the reservoir, and 13 (0.52 ha) in the downstream area. A total of 71 species were identified, of which 36.7 % were trees, 26.8 % shrubs, 18.3 % were herbs, and 4.2 % climbers. About 59 species of vascular plants, belonging to 39 families and 53 genera, were recorded upstream of the dam. 17 species comprising 15 families and 17 genera were recorded in the area that will be flooded by the reservoir and 21 species comprising 15 families and 18 genera were recorded in the riparian zone downstream of the dam. Comparison of species indicates that though there is no significant difference between the three sites in terms of species density (p = 0.345). The downstream region has more diverse and evenly distributed species compared to the upstream and reservoir areas. There was no significant difference in terms of species density and diversity in the adjacent and riverine parts of the upstream and downstream areas. Most of the species in the area downstream of the dam including Dodonea angustifolia, Ensete ventricosum, Syzygium guineense, Accacia spp., Combretum adengonium, and Combretum molle, which were found exclusively in the riverine part, are species that are normally found inhabiting riverine areas. This indicates that the majority of the downstream vegetation prefers moisture rich substratum. Flow history was examined to analyze the likelihood of disturbance in scenarios with and without flow regulation. The hydrological analysis shows that the dam may lead to reductions in maximum daily discharges and flood frequency. Reductions in flood peaks and over-bank flows could result in changes in species composition and diversity of plants growing in water or water rich substratum below the dam.